Pemanfaatan Apbs dan Geogebra untuk Meningkatkan Minat dan Hasil Belajar Matematika di SMP - Kucisti Ike Retnaningtyas Suryo Putro (Universitas Muhammadiyah Surakarta, 2016)
Many factors cause difficulty class VII SMP 12 Surakarta 2014/2015 study mathematics. In addition to the abstract mathematical characteristics, other factors causing difficulty in learning mathematics that students could come from within the students themselves (internal) or from outside the student (external). This resulted in low interest and mathematics learning outcomes. One reason is the lack of teachers in the optimal use of props, the media and the right approach that can make students interested, aroused, quickly catching and easy to understand the material given. To overcome this problem is presented based trash props (APBS) GeoGebra software combined with a scientific approach to the study of mathematics. This budgets material is all around us, it is easy to get, easy to be pursued, easy to make, inexpensive and very familiar with the students. While the software GeoGebra is also a very simple application to be downloaded for free. The scientific approach is an approach to learning that are tailored to the curriculum in 2013 that made the students as a learning center. Results of this class action is the use of GeoGebra software budgets combined with a scientific approach can increase interest and student learning outcomes VIIH semester grade 2014/2015 transformation of matter.